How do you factor completely #t^2-4t+3#?

2 Answers
Jun 12, 2016

Answer:

#(x - 3)(x -1)#

Explanation:

Find factors of 3 which add up to 4.
THe signs in the brackets will be the same (because of the +) they are both negative. (because of -4)

#(x - 3)(x - 1)#

Jun 12, 2016

Answer:

#t^2-4t+3=(t-1)(t-3)#

Explanation:

To factorize #t^2-4t+3#, we should split the middle term #-4# in two parts whose product is product of coefficients of other two terms i.e #1xx3=3#. These are #-3# and #-1#. Hence,

#t^2-4t+3#

= #t^2-3t-t+3#

= #t(t-3)-1(t-3)#

= #(t-1)(t-3)#